Beneficial and Harmful Products, Innovations and Denovations - Aslanova, Leona (Research Papers, 2024)
Is there more innovations or more denovations in Bulgaria? In asking this question we need to clarify the economic dependence between the two concepts. In this academic article we consider the introduction of a new economic concept, phenomenon and term „denovation“, which has the following principle characteristics: 1) the principle of antithesis – reducing or nullifying the impact of innovation; innovation works in the opposite direction to the economic impact of innovation on society; 2) the principle of the center and periphery – denovation always occurs in the center; 3) the principle of the speed of market penetration – denovation always enters and spreads faster than innovation.
Keywords: Entrepreneurship; Innovation; Denovation; Regress; Progress